Pengaruh Disiplin dan Kemandirian Terhadap Prestasi Belajar Siswa Kelas Atas SD Muhammadiyah 3 Nusukan Tahun 2015/2016 - Wardani, Eva Kusuma (2016)
This study aims to determine: (1) the influence of discipline on student achievement upscale SD Muhammadiyah 3 Nusukan year 2015/2016. (2) the effect of independence on student achievement upscale SD Muhammadiyah 3 Nusukan year 2015/2016. (3) the effect of discipline and independence together on student achievement upscale SD Muhammadiyah 3 Nusukan year 2015/2016. This research is quantitative research, design ex postfacto. The study population was the whole upscale SD Muhammadiyah 3 Nusukan. The technique of collecting data using questionnaires and documentation. Mechanical testing instrument covers the validity and reliability test. Data analysis technique used is multiple regression, t test, F test, the coefficient of determination and SR and SE. The study was preceded by technical prerequisite test is a test of normality and linearity test. Based on the results of multiple linear regression analysis obtained by the following equation: Y = 36.345 + 0.200 + 0.316. The results of this study can be concluded that: 1) there is the influence of the discipline of learning on student achievement upscale SD Muhammadiyah 3 Nusukan Year 2015/2016. 2) there is the influence of independent learning on student achievement upscale SD Muhammadiyah 3 Nusukan Year 2015/2016. 3) there is the influence of discipline and independence together on student achievement upscale SD Muhammadiyah 3 Nusukan Year 2015/2016. Variable discipline of learning contribute effectively amounted to 10.3% and variable independent learning contribute effectively amounted to 20.5%. so that total effective contribution given the two variables is 30.8%, while 69.2% is influenced by other variables not examined.